PELAKSANAAN PERKAWINAN MENURUT ADAT DAYAK NGAJU DI KECAMATAN TIMPAH KABUPATEN KAPUAS - Sakman; Offeny; Novialayu, Ela (PPKn, Fakultas Keguruan dan Ilmu Pengetahuan Universitas Palangka Raya, 2020)
The problem in this study is regarding the Implementation of Marriage According to Dayak Ngaju Customs in the District of Taya Kapuas District